Analisis elemen-elemen dasar dalam desain game My Talking Angela 2 berdasarkan kajian Ludologi - Endah Riana Endarini; Yolanda Georgia Andriani (Institut Seni Indonesia Yogyakarta, 2026)
This study aims to analyze the implementation of Teresa Dillon’s eight fundamental game elements and the ludological mechanisms in My Talking Angela 2, as well as to evaluate the effectiveness of its User Interface based on the six Gestalt principles. The research employs a descriptive qualitative method through 14 days of intensive observation, literature review, visual documentation, and a multi-stage data analysis process validated by triangulation to examine the game’s core elements, ludic interactions, and interface design. The findings indicate that My Talking Angela 2 incorporates all fundamental game elements through repetitive caregiving rules; a game world composed of independent ludic and extra-ludic areas that do not form an overarching narrative; a flat, non-progressive main character (Angela); and objects that function primarily as complements without influencing core progression. Its ludological mechanisms establish a casual gameplay loop without central events, in which activities and mini-games merely guide player actions without generating character development or long-term consequences. The game interface applies Gestalt principles to construct visual hierarchy, direct attention, and facilitate navigation with minimal text, supported by a bright color palette that creates an approachable and cheerful impression for both child and adult players. However, the consistency of the implemented game elements and Gestalt principles has not yet been empirically tested, indicating the need for further research through usability testing and user experience analysis.